Treatment of hyperhidrosis and the role of Botulinum Toxin Type A in therapy - a literature review - Szczuraszek, Hugo; Szczuraszek, Paulina; Sałata, Piotr; Olko, Paweł; Paluch, Michał; Licak, Gabriela; Żuchnik, Magda; Bętkowska, Paulina; Radulski, Jakub; Rybkowska, Agnieszka (Quality in Sport, 2023)
Introduction: Sweat secretion is a physiological process controlled by the autonomic nervous system, and it operates independently of our will. Primary hyperhidrosis is a disease characterized by excessive sweating, which is thought to result from localized hyperstimulation of sweat glands by cholinergic sympathetic nerve fibers. It can be associated with significant occupational, physical and emotional impairment, as well as significant difficulties in social situations and personal relationships. Available therapies are limited by their short-term efficacy and, in some cases, significant side effects that can expose patients to potentially serious complications. One treatment for primary hyperhidrosis is chemodenervation of the sweat glands using botulinum toxin type A. Objective: To review the current literature and recent reports on hyperhidrosis treatment therapies. To discuss the mechanism of action and the role of botulinum toxin in treatment, as well as the potential risks associated with undertaking treatment. Materials and method: Literature review of PubMed, Google Scholar and Science Direct Conclusions: Intradermal injection of botulinum toxin A is an effective and safe therapy for severe axillary, palmar, forehead, neck and foot hyperhidrosis. Current knowledge does not indicate that this therapy is associated with dangerous complications. Unfortunately, it is not a method that permanently solves the problem of sufferers.